Densifying (Hf0.2Zr0.2Ta0.2Nb0.2Ti0.2)C high‐entropy ceramics by two‐step pressureless sintering. Issue 1 (24th September 2021) - Yu, Duo; Zhang, Buhao; Yin, Jie; Wang, Yichen; Liu, Xuejian; Reece, Michael J.; Huang, Zhengren
Abstract: A pressureless two‐step sintering method was used to densify high‐entropy carbide (Ti0.2 Zr0.2 Hf0.2 Nb0.2 Ta0.2 )C, with high density and good mechanical performance. The material was heated up to 2200°C and subsequently soaked at 1900°C for 2–8 h with the incorporation of 2–4 wt.% phenolic resin. With increasing resin content, the large‐sized pores disappeared, and the average grain size decreased. However, with increased holding time from 2 to 8 h, the average grain and pore size did not change significantly, the density increased up to 96.2%, and evident grain growth of graphite was observed. The mechanical properties of (Ti0.2 Zr0.2 Hf0.2 Nb0.2 Ta0.2 )C with 4 wt.% phenolic resin addition and 8 h soaking at 1900°C were measured as follows: flexural strength 361±28 MPa, Vickers hardness 16.0±0.3 GPa, and elastic modulus 426±2 GPa.